The level of awareness on cash waqf in Kota Bharu / Syamimi 'Aziemah Mohd Abdullah - Mohd Abdullah, Syamimi 'Aziemah (Academy of Contemporary Islamic Studies, 2018)
The perception of the community has been synonymous with assuming that waqf only consists of a property that is permanent and durable. Cash waqf is a trust fund comprising the fees received by the community and is one of the alternative instruments in eradicating poverty among Muslims. However, cash waqf implementation is relatively slow, the existence of cash waqf is still a question mark by most individuals. This is because the issue of law which is still a public discussion even though the various fatwa has been issued. In this regard, this study will identify the Islamic view of cash waqf and analyze the level of awareness of the Muslim community on cash waqf through knowledge and promotion medium giving awareness to the community to implement cash waqf. The study was conducted based on secondry data namely books, journals and etc and primary data which is questionnaire on Muslim community in Kota Bharu district, Kelantan. The data obtained will then be analyzed using certain methods. Research findings show that knowledge and promotion factors are positively related to giving awareness and understanding of cash waqf. Although the Muslim community in Kota Bharu is aware and understand about cash wakaf, the majority still do not engage in the cash wakaf. This study is expected to be providing guidance to all parties in improving quality and performance as cash waqf, especially the MAIK in raising the awareness of the local community in order to increase the involvement in the cash waqf activities that can be accompanied by every community in improving welfare and reducing poverty. It can also be done by all levels of society and not just limited to the rich.